A Novel Dual-Phase Activation-Dependent Foot-Switch Mechanism for Surgical Energy Devices as an Asset in Early Surgical Training: A Proof of Concept Study. (February 2020) - Eisawi, Abdalla; Aung, Myat; Canelo, Ruben
Introduction . Many processes exist that limit or eliminate the incidence of adverse events in general surgery including the World Health Organization safety checklist. Technology and device advancement has a potentially expanding role in the context of surgical safety. Materials and Methods . A dual controlled accessory electrical diathermy footswitch ( Permissive diathermy foot switch device or PDf ) device concept was developed in an effort to improve patient safety in theatre and enhance opportunities in training. Electrical diathermy is only activated if the senior supervising surgeon and the novice surgeon simultaneously activate their interconnected footswitches. The activation of the PDf accessory footswitch device allows a senior surgeon to exert control on "initiation" of activation of diathermy devices operated by a novice surgeon ( foot on pedal ) as well as when desiring to deactivate the device ( foot off pedal ). Results . A process of designing and prototyping was initiated to define the purpose and the functionality of the PDf device up till the stage of a fully functioning prototype. The PDf device was constructed as a final working and tested prototype in association with the local medical engineering department at the Cumberland Infirmary in Carlisle. The device was on a nonbiological model to determine efficacy and safety and passed its laboratory testing phase and was deemed ready for clinical use. Conclusion . We demonstrated the feasibility and functionality of the PDf device and propose a positive role in surgical training in the context of early surgical training and specific circumstances where more control is needed.